Predictors of psychological adjustment, experienced parenting burden and chronic sorrow symptoms in parents of children with cerebral palsy - Whittingham, K.; Wee, D.; Sanders, M.; Boyd, Roslyn (2013)
Aim To investigate the role of child behaviour, parental coping and experiential avoidance in predicting the psychological outcomes of: (i) psychological symptoms; (ii) chronic sorrow symptoms; and (iii) experienced parenting burden in parents of children with cerebral palsy (CP). Method This study is a cross-sectional, correlational study. Ninety-four parents of children (aged 2-12 years) with CP (various levels of motor functioning GMFCS I-V) participated. Results Together, the three predictors of child behaviour, parental coping and experiential avoidance explained 36.8% of the variance in psychological symptoms with child behavioural problems and experiential avoidance as significant unique predictors. In addition, 15.8% of the variance in chronic sorrow symptoms was explained by the three predictors with experiential avoidance alone as a significant unique predictor. Lastly, the predictors together explained 24.3% of the variance in experienced parenting burden with child behavioural problems and experiential avoidance as significant unique predictors. Conclusions This study demonstrates a relationship between child behavioural problems and parental psychological symptoms and experienced parenting burden as well as a relationship between experiential avoidance and parental psychological symptoms, experienced parenting burden and chronic sorrow symptoms. © 2012 Blackwell Publishing Ltd.